Water resources management policy responses to land cover change in South East Asian river basins - Murdiyarso, Daniel (Cambridge University Press, 2004)
This chapter reviews several cases at the river basin scale where biophysical and socio-economic aspects are assessed and public policy-making processes are involved, with special reference to South East Asia. Examples from regional, national and local scales demonstrate the importance of a proper planning phase and at the same time conflict resolution during the implementation phase. It is emphasized that policy responses regarding land use options are needed at all scales and phases of management.